2016
DOI: 10.1002/admt.201600212
|View full text |Cite
|
Sign up to set email alerts
|

An Inkjet‐Printed, Ultralow Voltage, Flexible Organic Field Effect Transistor

Abstract: A very simple procedure for fabricating inkjet‐printed organic field effect transistors (OFETs) is reported. A reliable process for the deposition of a thin and uniform polymeric dielectric film of poly(4‐vinylphenol) (PVP) is established as a key factor for obtaining high performance devices operating at low voltages. To this aim, ink formulations, printing parameters, and cross‐linking processes are investigated. Morphological characterization of the fabricated films by means of contact profilometry and atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 48 publications
1
53
0
Order By: Relevance
“…[87][88][89][90][91][92][93][94][95][96][97][98] The lack of dipoles and hydrophobic nature of most polymer dielectrics may be beneficial for organic semiconductor deposition as well as the electrical performance and stability of OFETs. [87][88][89][90][91]94,95] In these devices, the ultrathin crystalline organic semiconductor brings a significantly low level of semiconductor bulk and interface trap density. The sharp turn-on slope in the subthreshold region (i.e., steep SS) and small V th of the OFET enable the device to reach the saturation state at a smaller gate bias.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 2 more Smart Citations
“…[87][88][89][90][91][92][93][94][95][96][97][98] The lack of dipoles and hydrophobic nature of most polymer dielectrics may be beneficial for organic semiconductor deposition as well as the electrical performance and stability of OFETs. [87][88][89][90][91]94,95] In these devices, the ultrathin crystalline organic semiconductor brings a significantly low level of semiconductor bulk and interface trap density. The sharp turn-on slope in the subthreshold region (i.e., steep SS) and small V th of the OFET enable the device to reach the saturation state at a smaller gate bias.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[106] Apart from high-k metal oxide dielectrics, applying solution-processed or initiated chemical vapor deposition (iCVD) polymer dielectrics with k value comparable or lower than SiO 2 can also reduce the operating voltage of OFETs. [87][88][89][90][91][92][93][94][95][96][97][98] The lack of dipoles and hydrophobic nature of most polymer dielectrics may be beneficial for organic semiconductor deposition as well as the electrical performance and stability of OFETs. [107] Although the dielectric constant of most polymers is intrinsically lower than that of metal oxides, several attempts can effectively operate the OFET at only a few volts.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…[6], [7] Among the different technologies, organic electronics is generally considered the most suitable for the complete exploitation of the potentialities of flexible electronics. Organic materials can be solution-processed at low temperatures by means of cost-effective techniques, [8]- [9] thus being perfectly suitable for large-area fabrication of electronic devices on flexible substrates, including plastic, [10]- [12] paper [13] and fabric. [14]- [16] Mechanical stability of organic electronic devices has been thoroughly explored in the last decade, in particular for Organic Field-Effect Transistors (OFETs), and it was found that, in this kind of structure, the mechanical sensitivity is mainly related to the morphological characteristics of the organic semiconductor film.…”
Section: Introductionmentioning
confidence: 99%
“…www.advmatinterfaces.de complementary inverters with channel length of 20 µm using reverse-offset printing. [18] The thinnest possible dielectrics are made of self-assembled layers. For instance, 30-100 nm thick dielectric films made of a polymer and a crosslinker can withstand electric fields of up to 4 MV cm −1 .…”
mentioning
confidence: 99%